Combination With Long-Acting Injectable Antipsychotics and Utilization of Nonstandard Formulations as Compliance Enhancing Methods for Clozapine Users: A Systematic Review and A Case Series. Issue 3 (3rd May 2022) - Mutlu, Emre; Karaçam Doğan, Melike; Ertuğrul, Aygün; Anıl Yağcıoğlu, A. Elif
Abstract: Background: Combining clozapine with a long-acting injectable antipsychotic (LAI) or using different, nonstandard formulations of the compound may improve treatment outcomes. We aimed to investigate the utility of the clozapine-LAI combination and different formulations of clozapine for compliance problems of clozapine treatment, and to describe a case series on the combined treatment. Procedures: We conducted a PubMed search with no date restriction. The number and length of hospitalizations, the results of clinical scales, and adverse events were recorded. We also present a case series of 18 patients using the clozapine-LAI combination. Data were collected from the medical charts and electronic records. Results: We extracted 9 records describing the use of the clozapine-LAI combination. The case reports and mirror-image studies showed a significant reduction in the number of hospitalizations, length of hospital stays, and number of visits to the emergency department on the combined treatment with no serious adverse events. We included 11 articles for clozapine formulations. The case reports and retrospective data suggested that short-acting intramuscular clozapine was often well tolerated and resulted in an increased acceptance of oral clozapine in the acute phase of illness. In our case series, illness severity and the number of hospitalization per year significantly decreased after the combined treatment, besides a significant improvement in the functioning scores. Hyperprolactinemia and extrapyramidal side effects were reported due to concomitant LAIs. Conclusions: Despite the encouraging evidence, the present data are preliminary and mostly based on retrospective studies, and oral-dissolving tablets or oral liquid formulations of clozapine have insufficient evidence for clinical practice. Well-designed, controlled, follow-up studies are needed for both clozapine-LAI combination and different formulations of clozapine.